Clonal Relationships among Shigella Serotypes Suggested by Cryptic Flagellin Gene Polymorphism - Coimbra, Roney S. (American Society for Microbiology, 2001)
The presence of cryptic fliC alleles in the genomes of 120 strains representative of the four Shigella species was investigated. One fragment was obtained by PCR amplification of fliC, with a size varying from 1.2 to 3.2 kbp, depending on the species or serotype. After digestion with endonuclease HhaI, the number of fragments in patterns varied from three to nine, with sizes of between 115 and 1,020 bp. Patterns sharing most of their bands were grouped to constitute an F type. A total of 17 different F types were obtained from all strains included in this study. A unique pattern was observed for each the following serotypes: Shigella dysenteriae 1, 2, 8, and 10 and S. boydii 7, 13, 15, 16, and 17. On the contrary, S. dysenteriae serotype 13 and S. sonnei biotype e were each subdivided into two different F types. S. flexneri serotypes 3a and X could be distinguished from the cluster containing S. flexneri serotypes 1 to 5 and Y. S. flexneri serotype 6 clustered with S. boydii serotypes 1, 2, 3, 4, 6, 8, 10, 11, 14, and 18 and S. dysenteriae serotypes 4, 5, 6, 7, 9, 11, and 12. Two other clusters were outlined: one comprising S. dysenteriae serotypes 3, 12, 13 (strain CDC598-77), 14, and 15 and the other one joining S. boydii serotypes 5 and 9. None of the 17 fliC patterns was found in the fliC HhaI pattern database previously described for Escherichia coli. Overall, this work supports the hypothesis that Shigella evolved from different ancestral strains of E. coli. Moreover, the method outlined here is a promising tool for the identification of some clinically important Shigella strains as well as for confirmation of atypical isolates as Shigella spp.